The image of youth in television advertising from Peru - Quinte Rodríguez, Silvia Liseti (2020)
The research aimed to characterize the image of youth shown in television advertising from Peru, defining the role assigned to young people in the advertising pieces of Peruvian television. The study, of basic type and simple descriptive design, took a sample of 100 advertising spots, broadcast during the months of July, August and September 2019. A youth image content analysis sheet, designed for the study, was applied as a data collection instrument. It was found that, predominantly, advertising shows young people of Caucasian and athletic phenotype and that stand out for their physical attractiveness, with roles of beauty, body care and the image itself, having pleasure as the main objective. It is concluded that the image of youth in national television advertising is discriminatory in the phenotype it represents; superficial and hedonistic, in the assigned roles, and homogenizing, in youth preferences.   DOI: https://doi.org/10.31876/sl.v4i1.53